2022
DOI: 10.1007/s12567-021-00415-y
|View full text |Cite
|
Sign up to set email alerts
|

Mission engineering for the RETALT VTVL launcher

Abstract: In the last decade, the rapid and successful development of reusable launch systems such as SpaceX’ Falcon 9 demonstrated both the operational feasibility of reusable launchers and their economic viability. The objective of recovering a launcher or a launcher’s booster requires to safely return the launch vehicle from orbital or sub-orbital conditions to a soft landing. To increase the reusability, decrease the turnaround time and reduce costs, a precise touchdown on a pre-defined landing site or on a floating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…However, not all configurations were tested at all Mach numbers. Alpha polars of ±10 • were tested in all test runs, which was defined according to the mission design needs described in [2]. Figure 12 shows a comparison of the Reynolds numbers of the flight configuration with the Reynolds numbers tested in TMK.…”
Section: Test Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not all configurations were tested at all Mach numbers. Alpha polars of ±10 • were tested in all test runs, which was defined according to the mission design needs described in [2]. Figure 12 shows a comparison of the Reynolds numbers of the flight configuration with the Reynolds numbers tested in TMK.…”
Section: Test Conditionsmentioning
confidence: 99%
“…2). A more detailed descriptions of the flight phases of the RETALT1 configuration can be found in [1] and [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Fig. 1 RETALT1 return mission concept [ 10 ]
Fig. 2 Main characteristics of the RETALT1 configuration as presented in Ref.
…”
Section: Overview Of the Retalt Reference Configurationsmentioning
confidence: 99%
“…A study by DEIMOS Space presented in Ref. [ 10 ] concluded that the angle of attack at which the vehicle should be trimmable during the aerodynamic phase should be up to 10°. Based on this condition and based on the reference trajectories presented in Ref.…”
Section: Design Changes Of the Retalt1 Configurationmentioning
confidence: 99%